Impact of age at the time of the first ST-elevation myocardial infarction on 10-year outcomes. A sub-analysis from the EXAMINATION EXTEND trial. (3rd October 2022) - Arevalos Rivas, V; Spione, F; Gabani, R; Ortega-Paz, L; Gomez-Lara, J; Jimenez-Diaz, V A; Jimenez, M; Jimenez-Quevedo, P; Diletti, R; Pineda, J; Campo, G; Silvestro, A; et al.
Abstract: Background: The aim of this post-hoc sub analysis of the EXAMINATION-EXTEND study was to analyze 10-year outcomes according to the age of the patient at the time of the first STEMI. Methods: Out of 1498 STEMI patients included in the EXAMINATION-EXTEND study, those with a previous history of atherosclerotic cardiovascular disease (coronary ischemic event, ischemic stroke, or previous coronary revascularization) were excluded for this analysis. The remaining 1375 patients were divided into three age groups: <55, 55–65 and >65 years. The primary endpoint was 10-year patient oriented composite endpoint (POCE) of all-cause death, any myocardial infarction (MI), or any revascularization. Secondary endpoints included the individual components of the primary endpoint, cardiac death, target vessel myocardial infarction (TVMI), target lesion revascularization (TLR), and stent thrombosis. The association between age and endpoints was adjusted for baseline confounders. Results: At 10-year follow-up, patients <55 years (Adjusted hazard ratio [HR]: 0.42, 95% CI: 0.33–0.53, p=0.001), and 55–65 years (Adjusted HR: 0.44, 95% IC: 0.35–0.56, p=0.001) showed lower risk of POCE compared with those >65 years, led by a lower incidence of all-cause death (<55: 5.8% vs. 55–65: 11.3% vs. >65 years: 40.67%, p=0.001). Cardiac death was more prevalent in the older group (<55: 3.5% vs. 55–65: 5.5% vs. >65 years: 21.3%, p=0.001). There were not significant differences in the incidence of TVMI, TLR and stent thrombosis among the different age groups. In the landmark analyses, between 5 and 10-year follow-up, young patients exhibited higher incidence of any revascularization (<55: 7.4% vs. 55–65: 4.9% vs. >65 years: 1.7%, p=0.001) and a trend towards a higher incidence of any MI (<55: 5.2% vs. 55–65: 3.6% vs. >65 years: 1.5%, p=0.064). No differences were found in any other endpoints. Conclusions: In patients with a first STEMI, advanced age was associated with high rates of POCE at 10-year follow-up, in particular, due to all-cause and cardiac death. Conversely, patients who presented at younger age exhibited a high risk of revascularization at long-term follow-up. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Abbott Vascular